From North Pole to Equator: Studies of Wild Life and Scenes in Many Lands - Brehm, Alfred Edmund, 1829-1884; Brehm, Horst, 1863-1917; Thomson, J. Arthur (John Arthur), 1861-1933; Thomson, Margaret R. (Salt Lake City, UT : Project Gutenberg, 2022)
"From North Pole to Equator: Studies of Wild Life and Scenes in Many Lands" by Alfred Edmund Brehm is a scientific publication written in the late 19th century. The work serves as a collection of observations and narratives drawn from the author$1 (Bs extensive travels and lectures, celebrating the diversity of wildlife and the beauty of natural landscapes encountered across different regions. The book highlights the connection between humans and nature, emphasizing the experiences of various animal species. The opening of the book features a preface explaining Brehm$1 (Bs intention to share his father's popular lectures. It begins with an ancient Scandinavian legend about the creation of the land, setting the stage for a vivid exploration of the Nordic landscape, particularly focusing on its fjords, mountains, and islands. Brehm's descriptive prose immerses the reader in the unique characteristics of Scandinavian geography, detailing the flow of rivers, the appearance of the rugged terrain, and the marine life that flourishes there. This introduction promises a deeply engaging and informative journey through the natural world, encouraging a greater appreciation for the intricate relationships that define our environment. (This is an automatically generated summary.)s
Introductory essay by the editor -- The bird-bergs of Lapland -- The tundra and its animal life -- The Asiatic steppes and their fauna -- The forests and sport of Siberia -- The steppes of inner Africa -- The primeval forests of Central Africa -- Migrations of mammals -- Love and courtship among birds -- Apes and monkeys -- Desert journeys -- Nubia and the Nile rapids -- A journey in Siberia -- The heathen Ostiaks -- Nomad herdsmen and herds of the steppes -- Family and social life among the Kirghiz -- Colonists and exiles in Siberia -- An ornithologist on the Danube.
Release date is 2022-05-21
Alan & The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Natural history; Africa -- Description and travel; Animal behavior; Siberia (Russia) -- Description and travel; Birds -- Lapland; Tundras; Ethnology -- Russia (Federation) -- Siberia; Birds -- Danube River